Introducing the International Journal of Marketing Education - IJME - Eliashberg, Josh; Moore, Marian (Senate Hall Academic Publishing, 2005)
Welcome to the launch issue of the International Journal of Marketing Education (IJME). This innovative new journal is devoted to enhancing marketing education worldwide by publishing and disseminating high quality refereed teaching materials, including articles on key developments in teaching methods, course and programmatic structure and new pedagogical frameworks for Marketing education. The scope of the journal is global and it encourages cross-disciplinary perspectives. The journal reports on and discusses advances in marketing education wherever they occur. The IJME complements other scholarly journals in the field by focusing exclusively on educational material.